1986
DOI: 10.1200/jco.1986.4.7.1058
|View full text |Cite
|
Sign up to set email alerts
|

High-dose continuous infusion folinic acid and bolus 5-fluorouracil in patients with advanced colorectal cancer: a phase II study.

Abstract: Encouraging results have recently been reported for studies using folinic acid in combination with 5-fluorouracil (5-FU) in the treatment of patients with gastrointestinal (GI) malignancies. Thirty-six patients with advanced colorectal cancer with unequivocal evidence of progression while treated with fluoropyrimidines were treated with a six-day continuous infusion of 500 mg/m2/d of folinic acid initiated 24 hours before a five-day course of 5-FU administered as an intravenous (IV) bolus of 370 mg/m2/d. An in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1988
1988
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…Using mainly systemic FU-LV and oxaliplatincontaining chronomodulated regimens, we have demonstrated the ability to convert 14% of patients from an unresectable status to a resectable situation, with a postoperative 5-year survival rate of 33%. [8][9][10] More recently, however, the addition of biologic agents (bevacizumab or cetuximab) to cytotoxic chemotherapy has increased the rate and extent of tumoral responses, [11][12][13] suggesting that the addition of these agents to second-line or higher line regimens could improve resectability rates in treatment-refractory patients. [3][4][5][6] Although the combination of systemic chemotherapy and liver surgery can convert a significant proportion of patients from a palliative situation to a potentially curative situation, the majority of initially unresectable liver metastases do not respond sufficiently to initial chemotherapy to become resectable.…”
Section: Introductionmentioning
confidence: 99%
“…Using mainly systemic FU-LV and oxaliplatincontaining chronomodulated regimens, we have demonstrated the ability to convert 14% of patients from an unresectable status to a resectable situation, with a postoperative 5-year survival rate of 33%. [8][9][10] More recently, however, the addition of biologic agents (bevacizumab or cetuximab) to cytotoxic chemotherapy has increased the rate and extent of tumoral responses, [11][12][13] suggesting that the addition of these agents to second-line or higher line regimens could improve resectability rates in treatment-refractory patients. [3][4][5][6] Although the combination of systemic chemotherapy and liver surgery can convert a significant proportion of patients from a palliative situation to a potentially curative situation, the majority of initially unresectable liver metastases do not respond sufficiently to initial chemotherapy to become resectable.…”
Section: Introductionmentioning
confidence: 99%
“…Using optimal regimens , objective tumour responses may be expected in 25-30% of cases and are generally of short duration. Second-line therapeutic options have long been very disappointing (Ahlgren et al, 1991;Bertrand et al, 1992) and until recently patients were usually not offered alternative treatment after 5FU failure. However, encouraging preliminary results have been recently published using continuous 5FU (Izzo et al, 1992) with response rates of 16%.…”
mentioning
confidence: 99%
“…Antitumor activity of S'dFUrd in humans is probably similar to that observed with S-FU [28,29]. However, at the posologies and schedules used in the clinics, the drug induced prohibitive neurologic toxicity and cardiac abnormalities which render its use extremely difficult in humans [28,29], There are new attempts at synthesis of other prodntgs Bertrand et al [39] 15 Budd et al [40] 53 54 Schmoll et al [41] 68 Petrelli et al [ of the 5'dFUrd-type. The aim is to produce a compound that would be a better substrate for uridine phosphorylase than 5'dFUrd, leading to enhanced release of 5-FU within the cell.…”
Section: Precursors Of 5-fumentioning
confidence: 94%
“…Since 1982, a number of phase I1 studies have been reported in patients with colorectal, gastric, and more recently, breast carcinomas. In colorectal carcinoma patients who were not previously treated with chemotherapy, the mean response rate calculated from 16 available studies [33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49] was 31%, ranging from 15-54% (Table I). In patients who Bruckner et al [35] Madajewicz et al I371 Cunningham et al [38] Byrne et al [50] Valone et al [51] Bertrand et al 1521 Laufman et al [44] Hines et al [ were previously treated with chemotherapy [33][34][35]37,38,44, the mean response rate obtained in nine trials was 15% (range, 0-50%) ( Table 11).…”
Section: Biochemical Modulations Of the Fluoropyrimidines At The Levementioning
confidence: 99%